Some novel additions to Schiffnerulaceous fungi from Kerala, India - M. HARISH, M.C. RIJU and D.K. AGARWAL, V.B. HOSAGOUDAR*, G.R. ARCHANA (Indian Phytopathology, 2008)
A new species, Sarcinella gmelinae on Gmelina arborea, Schiffnerula lagerstroemiae on Lagerstroemia microcarpa and S. actinodaphnes on Actinodaphne sp. collected from the forest areas of Kerala are described and illustrated.